A stepwise optimization strategy to formulate in situ gelling formulations comprising fluconazole-hydroxypropyl-beta-cyclodextrin complex loaded niosomal vesicles and Eudragit nanoparticles for enhanced antifungal activity and prolonged ocular delivery - Heba Elmotasem; Ghada E.A. Awad (Elsevier, 2020)
Fungal keratitis and endopthalmitis are serious eye diseases. Fluconazole (FL) is indicated for their treatment, but suffers from poor topical ocular availability. This study was intended to improve and prolong its ocular availability. FL niosomal vesicles were prepared using span 60. Also, polymeric nanoparticles were prepared using cationic Eudragit RS100 and Eudragit RL100. The investigated particles had adequate entrapment efficiency (EE%), nanoscale particle size and high zeta potential. Subsequently, formulations were optimized using full factorial design. FL-HP-β-CD complex was encapsulated in selected Eudragit nanoprticles (FL-CD-ERS1) and niosmal vesicles. The niosomes were further coated with cationic and bioadhesive chitosan (FL-CD-Nios-ch). EE% for FL-CD-ERS1 and FL-CD-Nios-ch formulations were 76.4% and 61.7%; particle sizes were 151.1 and 392 nm; also, they exhibited satisfactory zeta potential +40.1 and +28.5 mV. In situ gels were prepared by poloxamer P407, HPMC and chitosan and evaluated for gelling capacity, rheological behavior and gelling temperature. To increase the precorneal residence time, free drug and selected nano-formulations were incorporated in the selected in situ gel. Release study revealed sustained release within 24 h. Permeation through excised rabbits corneas demonstrated enhanced drug flux and large AUC0-6h in comparison to plain drug. Corneal permeation of selected formulations labeled with Rhodamine B was visualized by Confocal laser microscopy. Histopathological study and in vivo tolerance test evidenced safety. In vivo susceptibility test using Candida albicans depicted enhanced growth inhibition and sustained effect. In this study the adopted stepwise optimization strategy combined cylodextrin complexation, drug nano-encapsulation and loading within thermosenstive in situ gel. Finally, the developed innovated formulations displayed boosted corneal permeation, enhanced antifungal activity and prolonged action.